Croesus at Dodona: The Test of Oracles in the Oracular Context - Crosby, Daniel J. (Histos, 2022)
In this paper, I reinterpret Herodotus’ account of Croesus’ test of the oracles (1.46–9). By comparing the words of Croesus’ question with the oracular tablets from Dodona, I show that Croesus’ inquiry was troublingly ambiguous. Croesus meant ‘What do I happen to be doing right now?’ but in the oracular tablets, similar questions mean ‘What might I do to find fortune?’ I propose, therefore, that the other oracles could have offered Croesus advice about having fortune, which the king unwittingly discarded as not fitting his test, and I argue that this interpretation is more consonant with Herodotus’ view of oracles in the rest of the Histories.